GERAKAN SANTRI MENJAGA LINGKUNGAN DI PONDOK PESANTREN RAUDHATUL ULUM SAKATIGA OGAN ILIR - Muhammad Khaidir Arie1 (Jurnal Media Sosiologi (JMS), 2021)
This research is examines about the movement of the students to protect the environment in the Islamic boarding schools of Raudhatul Ulum Sakatiga Ogan Ilir. Problem in this research is to observe and analysed backround and student movement form of islamic boarding school Raudhatul Ulum as a concerted effort within poor and healthless environtment condition that may affect student health. This study using descriptive qualitative as research method. Data were collected by observation, interviews and documentation. This research using the theory of framing from William A. Gamson. Result of this research founded some reason that became a background for the student to keeping sanitation on their school. First reason that the studentpractice and apply the value and moral of hadist that they learn related to their act on keeping the cottage sanitation alsoinfluenceof the student to keep environtmet around their cottage and make it confortable and enchanted as well as way to protect themselves from disease. The movement form of students in keeping clean their cottage and school by mass cleaning movement based on specified time such as every Tuesday at afternoon and Friday in the morning, doing a picket in the morning, day and night, apply a zero waste movement, made a water filtration and garden.